Evaluasi Waktu Tunggu di Loket Pendaftaran BPJS Rumah Sakit Al Islam Bandung - Aditya Aditya; Eka Purwanda (Jurnal Simki Economic, 2023)
This study aims to find out how long the waiting time is required for BPJS patients who will register at Counter A of BPJS Al Islam Hospital Registration. This type of research is descriptive quantitative with data sources taken by the observation method or observations made in two days. From the calculations that have been done, if the BPJS registration counter opens the registration counter, it will be 2. So, the probability of an empty system is 0.49. Then, the average patient in the queue is 0.77 people per hour. The average patient waiting time was 0.08 people per hour, the average time spent in the system was 5.1 minutes and the average time spent by patients in the queue was 0.54 minutes. The results of this study indicate that Counter A BPJS Registration is still not optimal in serving patients who will register and also patients need a long time to wait in line.